VALUATION OF CONTRACT DEMAND VOLUME OF NEW GENERATION PRODUCT (NGP) CAVITY FILTER CIGARETTE PROJECT USING INCOME APPROACH IN CIGARETTE FILTER COMPANY (PT CFC) - Junaidi, Anang; Gunarta, I Ketut (Universitas Nahdlatul Ulama Surabaya, 2023)
PT CFC, a cigarette filter manufacturer, sells the latest patent productcapsule cavity sensation filter to MNC Korea's cigarette factory. MNC delivered latestview forecast demand contract, of 356.75 million cigarette filters in totals, periodJanuary 2023 to July 2024, which to be marketed in Asia and the Commonwealth ofIndependent State (CIS) countries. Hence, to decide the feasibility of the project,requires research and analysis whether the project is profitable or detrimental.Objective of this research are to assist PT CFC in taking decision of those aboveproject, by using 2 approach methods, 1). Project Management, aiming to get an initialoutlay . 2). Financial Valuation through income approaches (Initial Outlay, cash flow,terminal cash flow, working capital, PP, IRR and NPV). From the research study, theInitial Outlay it cost GBP 1,552,410 which generating from project managementthrough LM (logic Model), WBS (work Breakdown Structure) and AP (ActivityPlan)). Annual cash flow will be minus at the 1year of project started, by GBP 185K, but in the 2nd year positive of GBP 832K, overall project during contractdemand period will positive of GBP 647K and terminal cash flow at the end of theproject delivered GBP 1.471K. By using CAPM method PT CFC required return18.01%, contribute from risk free return 3,509%, beta coefficient 1.27, and anannualized return 15%. Capital structure, planned and decided to using 100% equity,which resulting of WACC 18.01%. According to above data, financial valuation couldbe define, the Payback Period achieved 1.2 years. Internal Rate of Return counted350% higher compare to WACC 18.01%. Net present value positive of GBP 1.739K.Hence refers to valuation parameter above concluded that, the project investment wasfeasible and can be continued into project execution.